Pro-poor intervention strategies in irrigated agriculture in Asia: poverty in irrigated agriculture: issues and options: Indonesia - Arif, Sigit; Maksum, Mochammad; Murtiningrum; Suparmi; Hartono, Slamet; Mawarni, Agnes; Rahardjo; Rochdiyanto, Saiful; Hussain, Intizar; Wijerathna, Deeptha (International Water Management Institute, 2004)
IWMI-ADB Project